TRADITIONAL CLOTHES AND THEIR MEANINGS FOR THE BONE SOCIETY - Masgaba, Masgaba (Kementerian Pendidikan dan Kebudayaan, 2020)
This study applies a descriptive qualitative approach which aims to describe the symbolic meanings of Bugis traditional clothes for the Bone society. Techniques of collecting data are interview, direct observation, and library research. The result study indicates that in term of model and material, the traditional clothes (traditional clothes and bridal clothes) have experienced a lot of changes at this time. In the past, the material of waju ponco’/waju bodo was from gauze cloth, but it has progressed, it made from organdy cloth like the cloth used by Indians. In term of color, the wearers of the traditional clothes could be identified their age and nobility easily in the past, but its rule is not longer valid now. Likewise, the men traditional clothes named songko’, it can also be used freely by anyone, there is no differences in the status of nobility degree for the wearers of songko’. Traditional clothes accessories are not only as sweetener for clothes, but also have symbolic meanings.